Trade openness and stock market volatility in the ASEAN-5 countries: New evidence using SUR. Issue 3 (1st September 2016) - Nikmanesh, Lida
ABSTRACT: The present study investigates the relation between trade openness and stock market volatility in the ASEAN-5 countries, using data of the composite price indices and trade openness in these countries from 1990 to 2013. A two-step methodology is employed. Firstly, the volatilities of stock indices are estimated using GARCH family. Then panel and the seemingly unrelated regression (SUR) methods are utilised to find the linkage between trade openness and stock market volatility. The results prove that the SUR method can efficiently handle certain limitations of the panel regression method in the present study. The results concerning the whole sample period demonstrate that trade openness affects the stock market volatility in Indonesia and Malaysia positively; and in Thailand negatively. Although the effect of trade openness on the Philippine and Singaporean stock market volatilities is not significant during the whole sample period, trade openness is found to influence stock market volatility in the Philippines and Singapore in the subsamples.